Regional income disparities in Malaysia: A stochastic convergence analysis - Muzafar Shah Habibullah; AM Dayang-Affizzah; Chin-Hong, Puah (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
For the last four decades, income disparities across states in Malaysia continue to be a matter of concern. The existence of regional inequalities and the prospect that these inequalities may widen were recognized by the Malaysian government. The eight volumes of the 5-Year Malaysia Plan reflect the determination of the Malaysian government in alleviating if not totally eradicating the problem of regional or state level imbalances. The recent Ninth Malaysia Plan has again emphasized regional development policies in bridging the gap of regional disparities for the next five years. Using annual data for the period 1965 to 2003, the stochastic convergence definition suggested by Bernard and Durlauf (1995), univariate unit root tests suggested by Oxley and Greasley (1995) and panel unit root testing procedures proposed by Levin et al. (2002), Im et al. (1997) and Maddala and Wu (1999), our findings strongly support the stochastic convergence of catching up hypothesis for six regions in Malaysia. An important implication of this study is that Malaysia’s regional development policies, on average, have had a positive impact on the per capita income in all of the six regions.